2019
DOI: 10.1186/s12885-019-5969-6
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcome and potential prognostic factors in primary squamous cell carcinoma of the parotid gland

Abstract: s Background Primary parotid squamous cell carcinoma (SCC) is an uncommon tumour, and there is limited data on its prognosis and treatment. The goal of the current study was to analyse the potential prognostic factors and clinical outcomes for this tumour type. Methods Consecutive patients with surgically treated primary parotid SCC were retrospectively enrolled in this study. The primary end point was locoregional control (LRC) and disease-specific surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 30 publications
9
36
0
Order By: Relevance
“…These authors found that the parotid gland was most likely to be involved, that 87.5% of the diseases were low or intermediate grade, and that most of the patients were staged as T1 or T2. Similar findings were also noted in the current study; moreover, both PNI and LVI have been found to be important prognostic factors ( 28 , 29 ). We are the first to report the rates of PNI and LVI in secondary patients, which were similar to those in primary patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These authors found that the parotid gland was most likely to be involved, that 87.5% of the diseases were low or intermediate grade, and that most of the patients were staged as T1 or T2. Similar findings were also noted in the current study; moreover, both PNI and LVI have been found to be important prognostic factors ( 28 , 29 ). We are the first to report the rates of PNI and LVI in secondary patients, which were similar to those in primary patients.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the significance of tumor stage and cervical nodal status has been widely analyzed. Both Fang et al ( 29 ) and Seng et al ( 32 ) reported that high tumor stage and neck lymph node metastasis were related to poorer survival, and our results also support this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Nineteen studies were included (Figure 1). 11‐13,20‐35 There were no prospective studies identified. Instead, all studies were retrospective and noncomparative trials.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were classified medium quality (5‐8 points) and seven studies as high quality (9‐12 points). It is important to note that nine of the studies came from the same institution, the Zhengzhou University, China, with varying time periods, inclusion criteria, and the outcome measures 13,21‐24,28,31,32,35 . All but one study were single institutional noncomparative cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Radiotherapy can be used as adjuvant therapy in patients with risk factors [2]. Squamous cell carcinomas (SCC) of the parotid gland have a worse prognosis as compared to other malignant tumours of the parotid gland, such as adenoid cystic, mucoepidermoid, and acinic cell carcinomas [8]. Tumorigenesis of squamous cell carcinoma of the parotid gland [9] is still under discussion: While some might consider primary SCC of the salivary glands as being non-existent, the vast majority of patients report on a previous cutaneous squamous cell carcinoma (CSCC) in the head and neck area [10,11], typically 1 year after onset of disease [12].…”
Section: Introductionmentioning
confidence: 99%